What Kind of Students Attend Cyber Schools? Pandemic Enrollment as Evidence of Negative Selection - Kingsbury, Ian; Beck, Dennis; Bradley-Dorsey, Martha (Frontiers in Education, 2022)
Fully online virtual schools have consistently underperformed academically compared to brick and mortar schools. Scholars debate the extent to which these differences are due school quality or the type of student that attends virtual schools. The large number of students who enrolled in virtual schools during the COVID-19 pandemic provides a unique opportunity to revisit this debate, as the phenomenon plausibly attenuates negative selection into virtual schools. Previous research concluded that a virtual school COVID cohort resembled prior groups demographically but reported greater success at their prior in-person schools and in cyber schools, however, it offered only limited insight into their academic performance at their virtual school. We use data from a large cyber charter network (“Countrywide Cyber”) to assess whether students who enrolled in full time virtual schools due to COVID-related concerns performed better on entry diagnostic assessments. Results indicate that students who enrolled due to COVID-19 were stronger academically, corroborating recent descriptive research. The implications of these results for practice and policy are discussed.